Negative externalities as the engine of growth in an evolutionary contexr - Angelo Antoci; Stefano Bartolini (Fondazione Eni Enrico Mattei (FEEM), 1999)
We present a simple growth model which has two original features: the strategic context considered, which is an evolutionary game, and the growth mechanism described, in which growth is caused by negative externalities. The emphasis in this growth mechanism is evidently different from that placed on positive externalities by current endogenous growth models. In this model welfare depends on three goods: leisure, a free environmental renewable resource, and a non-storable output. The environmental resource is subject to negative externalities, that is, it is deteriorated by the production of the output. Faced with a forced reduction of the resource, agents may react by increasing the labour supply in order to produce and consume substitutes for the diminishing resource, i. e. they can raise their defensive expenditures. The increase in production and consumption that follows, i.e. growth, generates a further deterioration of the environmental resource, thus giving rise to a self-feeding growth process. The conditions under which multiple equlibria and Pareto-worsening growth dynamics arise, are analysed. Besides showing the logical possibility that negative externalities are the engine of growth, we suggest that the case analysed may be of practical relevance, i.e., that negative externalities may play an important role in many episodes of growth. This role is widely recognised by social sciences other than economics. We suggest that the model may be interpreted as a push development model and that it may also contribute to explain some aspects of growth in advanced countries.
Keywords: 330; Externer Effekt; Stochastisches Wachstumsmodell; Theorie; Evolutionäre Spieltheorie